The Retrocatalography Project: Combining AI with the Microsoft Power Platform at the Royal National Library of Belgium - Schumann, Anna-Lea; Mergel, Ines (Springer, 2025)
The Royal National Library of Belgium (KBR) collects all Belgian publications and safeguards the country’s cultural and historical heritage. Given the increasing volume of records and the existence of records that are only catalogued on paper cards, there emerged a need for an AI-based solution. In response, KBR initiated a project called Retrocatalography, collaborating with the external service provider Initum. This partnership resulted in the development of an AI-based cataloguing solution which was created in just 10 days. Built on the Microsoft Power Platform, this low-code application is capable of gathering information from a book’s cover, archiving it, and verifying the details. In addition, KBR developed the Allez app in-house to scan library records. Volunteers use the app by assisting in the verification process to ensure accuracy of the records data. The AI-based solution went live in October 2022, with strong support from top management of the library. Along the way, KBR encountered several challenges, including staff shortages, time constraints for integrating the system into daily operations, and various technical difficulties. Overall, the AI-based solution transforms the workflow of librarians at KBR. It has made cataloguing books more efficient, ultimately enhancing the quality of the library services.
Keywords: Artificial Intelligence; AI; Royal Library of Belgium; KBR; National Library; Retrocatalography; Microsoft Power Platform; Allez app; Low-code; Volunteers; fi=Julkisjohtaminen|en=Public Management|